keV Electron Microbursts above Auroral Arcs - Matsumoto, Haruya; Kaya, Nobuyuki; Yamagishi, Hisao (1981)
P(論文) Electron microbursts in the energy range less than 10keV were directly observed at local night by a S-310JA rocket launched into a corona-type aurora from Syowa Station, Antarctica. Microbursts occurred in trains, and had an average duration of 0.1 second. The flux increase ranged from a factor of two to ten. departmental bulletin paper